THE WAYS OF PRODUCTION OF FOAMED ALUMINIUM, FIELDS OF ITS APPHCATION AND RAW OF PECULIARITIES OF MECHANICAL TREATM ENT - Kalinichenko; A. S. Kalinichenko (Литьë и металлургия)
The authors of the article give the review of the existing technologies of the foam aluminium alloys production and their physical-mechanical characteristics, what is of a certain interest not only of metallurgists but of designers as well.